Practice-based research with psychologists-in-training: presentation of a supervision model and use of routine outcome monitoring (Investigación basada en la práctica con psicólogos en formación: presentación de un modelo de supervisión y uso de la monitorización rutinaria de resultados). Issue 3 (2nd September 2022) - Valdiviezo-Oña, Jorge; Granja, Eduardo; Cuadros-López, Alejandra; Valdivieso-Meza, Grace; Evans, Chris; Paz, Clara
ABSTRACT: Objective: To present the training and care model used in a university psychological care centre and its outcomes, framed in the Practice-Based Evidence paradigm. Methods: Naturalistic study on the results of 161 clients seen between 2018 and 2020 who completed the Clinical Outcomes in Routine Evaluation — Outcome Measure. Statistically significant change was measured using multilevel regression models and reliable and clinically significant change was measured by applying the Jacobson and Truax approach. Results: On average, clients were 29.47 years old ( SD = 10.11) and the median number of sessions that they attended was five. CORE-OM scores decreased 0.05 points per session and trajectories of change were identified as diverse. Of the total number of clients, 29.4% showed reliable and clinically significant change and 45.1% showed at least reliable change. Discussion: The routine outcome monitoring results from this centre allow us to refine certain training and supervision activities to improve quality-of-care indicators.